Electromagnetical Efficiency of the Six-phase Winding - Buksnaitis, J. (Elektronika ir Elektrotechnika, 2012)
The investigation of electromagnetical efficiency of the two-layer preformed six-phase winding is presented. At first the variation of phases of the six-phase windings was determined and, on the basis of the theory of three-phase windings, the development of the electrical circuit of the analyzed winding was formed. In order to determine the harmonic spectrum of rotating magnetomotive force created by the six-phase winding the instantaneous space function of rotating magnetomotive force was formed by using the created circuit and instantaneous values of the phase currents in the moment of time t = 0. The harmonic analysis of this function was performed and according to its results the electromagnetical efficiency factor of the analyzed six-phase winding was calculated. The obtained factor was compared to the electromagnetical efficiency factor of the two-layer preformed three-phase winding of analogous parameters and it was determined that it is 8,64 % higher than in the three-phase winding case. Additionally it was obtained that the amplitude value of the fundamental harmonic of rotating magnetomotive force of the analyzed six-phase winding is 1,983 times higher that the amplitude value of rotating magnetomotive force of the analogous three-phase winding. This means that the power factors of the alternating current electrical machines with the six-phase windings should be notably higher compared to the three-phase machines. Ill. 2, bibl. 8, tabl. 6 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.119.3.1352